A transformation grammar-based methodology for housing rehabilitation - Eloy, S. (2015)
The goal of this research is to rehabilitate the existing housing stock to meet the new needs of dwellers in the current information society and the consequent need for the integration of Information, Communication and Automation Technolo-gies (ICAT) in living areas. This article focuses on the use of both shape grammar and space syntax as tools to identify and encode the principles and rules behind the adaptation of existing houses to new requirements. The idea is to use such rules as part of a methodolo-gy for the rehabilitation of existing dwellings.